Isolation of cDNA encoding phytoene synthase (crtB) in carrot (Daucus carota L. ssp. sativus) - Abdul Halim, Iman; Mohammed, Abdulkarim Sabo; Radu, Son; Tan, Wen Siang (WFL Publisher, 2014)
Daucus carota is one of the most renowned, widely available and a cheap source for carotenoid. Carotenoids have interesting pigment properties andmore importantly, are the beneficial effects it has on human health. Carotenoid gene isolated from natural sources has been used to produce carotenoid via microbial fermentation because of the dramatic increase in demand. Furthermore, there are advances in the metabolic engineering of insertion of these genes in food-grade non-producer microbes thus producing high quality and cheap natural dietary carotenoid compared to synthetic carotenoid. In order to catalyze the dimerization of two molecules of geranyl-geranyl pyrophosphate (GGPP) to phytoene, phytoene synthase (CrtB) plays an important rate limiting function for the synthesis of β-carotene. It catalyzes the first step of the carotenoid biosynthetic pathway. cDNA of crtB gene was synthesized from 18S (750 – 1000 bp) and 28S (1000 – 1500 bp) total RNA extracted from the fleshy tuber of D. carota. Amount of total RNA extracted ranged from 3.45 to 4.20 µg/ml. A total of high quality cDNA of crtB ranged from 1.90 to 2.90 µg/ml was successfully isolated at the length of 930 bp, which showed very low contamination of protein and polysaccharide. A high quality cDNA encoding phytoene synthase crtB isolated from cheap source such as D. carota may fulfill the high demand of natural carotenoid and can be a huge contributor for higher profit for the industry, safer and more importantly, therapeutically more effective source for health benefit than synthetic carotenoids, which are more difficult to be absorbed by the body.